Right Ventricular Doppler Echocardiographic Study of Indeterminate Form of Chagas Disease - Furtado,Rogério Gomes (2015)
Background: Patients with indeterminate form of Chagas disease/cardiac normality (ICD/CN) exhibited normal electrocardiograms and chest X-rays; however, more sophisticated tests detected some degree of morphological and functional changes in the heart. Objective: To assess the prevalence of systolic and diastolic dysfunction of the right ventricle (RV) in patients with ICD/CN. Methods: This was a case–control and prevalence study. Using Doppler two-dimensional echocardiography (2D), 92 patients were assessed and divided into two groups: group I (normal, n = 31) and group II (ICD/CN, n = 61). Results: The prevalence of RV systolic dysfunction in patients in groups I and II was as follows: fractional area change (0.0% versus 0.6%), mobility of the tricuspid annulus (0.0% versus 0.0%), and S-wave tissue Doppler (6.4% versus 26.0%, p = 0.016). The prevalence of global disorders such as the right myocardial performance index using tissue Doppler (16.1% versus 27.8%, p = 0.099) and pulsed Doppler (61.3% versus 68%, p = 0.141) and diastolic disorders such as abnormal relaxation (0.0% versus 6.0%), pseudonormal pattern (0.0% versus 0.0%), and restrictive pattern (0.0% versus 0.0%) was not statistically different between groups. Conclusion: The prevalence of RV systolic dysfunction was estimated to be 26% (S wave velocity compared with other variables), suggesting incipient changes in RV systolic function in the ICD/CN group.